Black men's awareness of peripheral artery disease and acceptability of screening in barbershops: a qualitative analysis - Tyler Coy; Ellen Brinza; Sarah DeLozier; Heather L. Gornik; Allison R. Webel; Christopher T. Longenecker; Khendi T. White Solaru (BMC, 2023)
Abstract Introduction Peripheral artery disease (PAD) disproportionately burdens Black Americans, particularly Black men. Despite the significant prevalence and high rate of associated morbidity and mortality, awareness of and treatment initiation for PAD remains low in this demographic group. Given the well-established social cohesion among barbershops frequently attended by Black men, barbershops may be ideal settings for health screening and education to improve awareness, early detection, and treatment initiation of PAD among Black men. Methods A qualitative study involving 1:1 participant interviews in Cleveland, Ohio assessed perspectives of Black men about barbershop-based screening and education about PAD. Inductive thematic analysis was performed to derive themes directly from the data to reflect perceived PAD awareness and acceptability of screening in a barbershop setting. Results Twenty-eight African American/Black, non-Hispanic men completed a qualitative interview for this analysis. Mean age was 59.3 ± 11.2 years and 93% of participants resided in socioeconomically disadvantaged zip codes. Several themes emerged indicating increased awareness of PAD and acceptability of barbershop-based screenings for PAD, advocacy for systemic changes to improve the health of the community, and a desire among participants to increase knowledge about cardiovascular disease. Conclusions Participants were overwhelmingly accepting of PAD screenings and reported increased awareness of PAD and propensity to seek healthcare due to engagement in the study. Participants provided insight into barriers and facilitators of health and healthcare-seeking behavior, as well as into the community and the barbershop as an institution. Additional research is needed to explore the perspectives of additional stakeholders and to translate community-based screenings into treatment initiation.